A randomized interventional study on clinico-surgical outcome of vaginal hysterectomy with hydro dissection versus without hydro dissection - Sharma, Devika; Jhajharia, Neelam; Banerjee, Krishna Priya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Hysterectomy is one of the most common gynaecological surgeries performed worldwide. The common indications for hysterectomy are benign like symptomatic uterine leiomyomas, endometriosis etc. We compare clinico-surgical outcome of vaginal hysterectomy with hydro dissection versus without hydro dissection. Methods: Women attending Gynae OPD or admitted was included in study and 30 cases taken in each group. Group A: Vaginal hysterectomy with hydro dissection. Hydro Dissection was done by about 50 ml to 100 ml of saline was infiltrated under pressure all around the cervix, just under vaginal mucosa below the bladder sulcus. Group B: Vaginal hysterectomy without hydro dissection. Results: The mean age of cases in Group-A was 49.63±8.91 yrs and in Group-B was 48.03±5.39 yrs was uniform. The mean operative time in Group-A was 49.07±6.46 min and in Group-B was 53.40±5.87 min which was statistically significant (p-value = 0.009). The mean intraoperative blood loss in Group-A was 89.77±6.49 ml and in Group-B was 97.67±12.93 ml which was statistically significant (p-value = 0.005). The mean level of change in Hb was 0.70±0.29 gm/dl in Group-A and was 1.01 ± 0.43 gm/dl in Group-B, which was statistically significant (p-value = 0.002). Conclusions: Hydro dissection with saline in vaginal hysterectomy is associated with significant reduction in duration of surgery, blood loss and lower mean level of change in Hb.